Pengaruh Kompensasi Finansial dan Non Finansial Terhadap Kinerja Karyawan - Franfascal Niko Denal Khaq; Beny Mahyudi Saputra; Nurhidayati Nurhidayati (JURNAL MANAJEMEN DAN BISNIS, 2022)
This study explains the impact of compensation, namely financial and non-financial on employee performance at UD. Sumber Rejeki. The subjects in the study were all employees UD Sumber Rejeki, totaling 50 peoples. Then obtained a sample of 40 people, namely permanent employees UD. Sumber Rejeki using purposive sampling technique. Data were obtained through distributing questionnaires, conducting observations, interviews, and literature studies. Data analysis techniques used by researchers are validity, reliability, classical assumptions, multiple linear regression analysis, and hypothesis testing. From the results of the test that has been carried out, it is found that financial and non-financial compensation has a significant influence on employee performance. Keywords: Employee Performance, Financial Compensation, Non-Financial Compensation